Effects of o,p'-DDE, a Mitotane Metabolite, in an Adrenocortical Carcinoma Cell Line - Camila Bach; Claudia Rita Corso; Alan de Almeida Veiga; Mariana Martins Paraizo; Lauro Mera de Souza (MDPI AG, 2022)
In South Brazil, the incidence of pediatric adrenocortical carcinoma (ACC) is higher than in other regions and countries worldwide. The ACC treatment includes therapy with mitotane, the only adrenolytic drug approved by the FDA. The mitotane metabolism occurs via two main reactions: the β-hydroxylation, which yields the final product o,p'-DDA, and the α-hydroxylation, which will give the final product o,p'-DDE. It is speculated that o,p'-DDE may be an active metabolite since it has a cytotoxic effect on adrenocortical carcinoma cells (H295R). No further studies have been conducted to confirm this hypothesis; however, it was found that mitotane and its metabolites are present at significantly different concentrations in the plasma of the patients. Our study aimed to assess the in vitro effects of o,p'-DDE and o,p'-DDD in cell death pathways, oxidative parameters, and interaction with adrenal CYP's involved in the steroidogenic process in the H295R cell line. It was found that o,p'-DDE had a different effect than the o,p'-DDD on apoptosis, inhibiting this cell death pathway, but it promotes cell necrosis at higher concentrations. In contrast to o,p'-DDD, the o,p'-DDE did not have effects on the different oxidative parameters evaluated, but exhibited stimulatory interactions with steroidogenic CYP's, at intermediate concentrations. Therefore, we demonstrated important cell effects of o,p'-DDE; its plasma levels during mitotane therapy should be monitored as an important therapeutic parameter.